RE: Contribution of Fecal Calprotectin and Fecal Immunochemical Tests to the Evaluation of Patients with Ulcerative Colitis - , Tingpeng Hu, Zhimei Zhang, Fusheng Song, Wenguang Zhang, Jun Yang (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Hu T, Zhang Z, Song F, Zhang W, Yang J. RE: Contribution of fecal calprotectin and fecal immunochemical tests to the evaluation of patients with ulcerative colitis. Turk J Gastroenterol. 2024;35(6):511.